2018
DOI: 10.22246/jikm.2018.39.2.97
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Co-Administration of Herbal and Western Medicines to Hospitalized Patients with Osteoarthritis

Abstract: Objectives: The combined use of herbal and Western medicine is increasing. However, herbal medicine is highly likely to interact with Western medicine making it important to understand the effects of co-administration. This study investigates the ratio of patients who take Western medicine with herbal medicine, the types of medicines commonly prescribed together, and the results of hospital examinations. Methods: We investigated patients who were hospitalized at Kyung Hee University Korean Medical Hospital for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In a recent study, liver function tests were performed at admission and discharge in a group of osteoarthritis patients administered herbal medicine versus a group administered a herbalconventional medicine combination. 34 The results from that study showed that, although no differences in liver function were observed between the 2 groups, the patients who showed a slight increase in γ -GT levels in the herbal-conventional drug combination therapy group were all taking acetaminophen. 34 Taken together, our results indicate that further studies with long-term dosing and DILI monitoring, assisted by measurements of serum miR-122 levels, may be helpful in investigating the effects of Ojeok-san on potential acetaminopheninduced liver injury.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In a recent study, liver function tests were performed at admission and discharge in a group of osteoarthritis patients administered herbal medicine versus a group administered a herbalconventional medicine combination. 34 The results from that study showed that, although no differences in liver function were observed between the 2 groups, the patients who showed a slight increase in γ -GT levels in the herbal-conventional drug combination therapy group were all taking acetaminophen. 34 Taken together, our results indicate that further studies with long-term dosing and DILI monitoring, assisted by measurements of serum miR-122 levels, may be helpful in investigating the effects of Ojeok-san on potential acetaminopheninduced liver injury.…”
Section: Discussionmentioning
confidence: 90%
“…No clinically significant findings were observed in the safety and tolerability assessments, including AE monitoring. In a recent study, liver function tests were performed at admission and discharge in a group of osteoarthritis patients administered herbal medicine versus a group administered a herbal‐conventional medicine combination . The results from that study showed that, although no differences in liver function were observed between the 2 groups, the patients who showed a slight increase in γ‐GT levels in the herbal‐conventional drug combination therapy group were all taking acetaminophen .…”
Section: Discussionmentioning
confidence: 99%
“…Herbal preparations are relatively safe since they are based on traditionally used prescriptions; however, they can cause synergies or drug interactions when administered in combination with other medications. Studies that show this have included interactions with certain drugs or diseases such as antiplatelet drugs and osteoarthritis, reporting that a combination www.journal-jop.org of herbal preparations and medicines is relatively safe [4,5].…”
Section: Introductionmentioning
confidence: 99%